Myth and Society in Ancient Greece - Vernant Jean-Pierre (Zone Books, 1990)
A complex and previously unexplored intersection of the religious, social and political structures of ancient Greece. Introduction, The Class Struggle, City-State Warfare, Marriage, Social History and the Evolution of Ideas in China and Greece from the Sixth to the second Centuries B. C., The Society of the Gods, The Pure and the Impure, Between the Beasts and the Gods, The Myths of Prometheus in Hesiod, The Reason of Myth, Notes.